Lung Inflammation - Chung Ong, Kian (IntechOpen, 2014)
In order to perform its function in gas exchange, the lungs and all components of the respiratory system are constantly exposed to pathogens, toxins, pollutants, irritants, and allergens in the environment. Lung inflammation involves an array of mechanisms to defend the lung against these extrinsic agents and to repair injured tissue. Additionally, the lungs are a frequent target at risk to conditions associated with systemic inflammation that cause multi-organ damage. The inflammatory reaction in the lung is a complex and dynamic process, and our understanding in this field is rapidly progressing. Further elucidation of the complexity of inflammation will likely improve the clinicians approach to as well as the treatment of a myriad of lung disorders. The chapters in this book are selected topics of current interest in lung inflammation.